Exploring digital strategies used for English First Additional Language reading by Grade 4 teachers: A case of Thohoyandou Cluster - Mulaudzi, Israel Creleanor (My University, 2025)
This study, grounded in the pragmatist paradigm, employs a mixed-methods approach underpinned by both positivist and interpretivist paradigms to investigate digital strategies for teaching English First Additional Language (EFAL) reading to Grade 4 learners in the Thohoyandou Cluster. A convergent parallel design was used to integrate quantitative and qualitative findings. The study is framed by the Technology Acceptance Model (TAM), alongside Shulman’s Pedagogical Content Knowledge (PCK), Vygotsky’s sociocultural theory, Constructivist Learning Theory, and Cognitive Load Theory. It aimed to explore how digital strategies can help address EFAL reading difficulties. One hundred Grade 4 EFAL teachers completed questionnaires for the quantitative phase, while ten teachers were purposively selected for semi-structured interviews and classroom observations in the qualitative phase. Data analysis involved SPSS Version 29 for quantitative data and thematic analysis for qualitative data. Findings suggest that digital strategies enhance learner engagement and language proficiency, contributing to a more dynamic and inclusive EFAL reading programme. However, systemic difficulties such as limited digital infrastructure and insufficient teacher training hinder full implementation. The study recommends that policymakers invest in targeted professional development to build teachers’ digital and pedagogical skills.
Ph. D. in English Language Teaching (ELT)
Department of English. Media Studies and Linguistics
Keywords: Digital strategies; UCTD; EFAL reading difficulties; Technology Acceptance Model; Mixed-method research; Convergent parallel design; 372.60440968257; English language-- Study and teaching (Elementary) -- South Africa -- Limpopo; English language -- Study and teaching (Elementary) -- Technological innovation -- South Africa -- Limpopo; Educational technological -- South Africa -- Limpopo; Teaching -- Aids and devices -- South Africa -- Limpopo; Computer -assisted instruction -- South Africa -- Limpopo; Teaching machines -- South Africa -- Limpopo